Innovative framework for the development of the electrical industry of Ukraine - Veres Somosi, Mariann; Kobielieva, Tetiana (NTU "KhPI", 2015)
The report discusses issues of innovative development of industrial enterprises. Recommendations the authors relate the electrical business. Analyzed in detail the most important definitions of innovation: innovation, technology and intellectual property.
Keywords: technology; intellectual property; electrical enterprises